The correction of skilled athletes' constitution, specializing in bodybuilding in the preparatory period of the annual cycle. - Usychenko Vitalij Viktorovich (Kharkov National Pedagogical University, 2011)
The program of correction of build of highly skilled bodybuilders is developed. In researches took part 17 bodybuilders of high qualification. In examination the judges of international and national category were involved in bodybuilding. The biomechanics monitoring of build of sportsmen is conducted. Practical recommendations are developed in relation to the directed correction of build of highly skilled bodybuilders.